Digital Legal Education and Cybersecurity Awareness: A Bibliometric Study on Student Behavior - Sautunnida, Lia; Ridayani, Ridayani; Khairani, Khairani; Kurniasari, Eka; Utami, Anta Rini; Fajri, Iwan (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2024)
This study analyzes current trends in the integration of digital technologies with legal education and their impact on cybersecurity awareness among students. Through a bibliometric approach, the research identifies challenges, opportunities, and future directions in digital legal education, emphasizing the importance of a holistic approach that encompasses technical, digital rights, and ethical dimensions. While technology is increasingly embedded in legal education, human-centeredness and ethical considerations remain underrepresented in cybersecurity curricula. The findings reveal that current cybersecurity education predominantly focuses on technical and legal aspects, thereby neglecting critical humanistic factors necessary for comprehensive training. This paper underscores the need for more interactive and innovative educational strategies, such as collaborative learning and virtual reality simulations, to bridge the skills gap and adequately prepare students for the digital challenges of the modern world. Future research should further explore these strategies to enhance the effectiveness of cybersecurity education within legal studies, equipping students to navigate the complexities of a digitally driven age.